2012
DOI: 10.1101/lm.025973.112
|View full text |Cite
|
Sign up to set email alerts
|

Procedural learning and associative memory mechanisms contribute to contextual cueing: Evidence from fMRI and eye-tracking

Abstract: Using a combination of eye tracking and fMRI in a contextual cueing task, we explored the mechanisms underlying the facilitation of visual search for repeated spatial configurations. When configurations of distractors were repeated, greater activation in the right hippocampus corresponded to greater reductions in the number of saccades to locate the target. A psychophysiological interactions analysis for repeated configurations revealed that a strong functional connectivity between this area in the right hippo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
41
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(47 citation statements)
references
References 51 publications
6
41
0
Order By: Relevance
“…These results, jointly with the current data, are compatible with the hypothesis that contextual cuing of visual search is not supported by uncontrollable attentional orientation towards the target in repeated trials. This idea will benefit from future research examining the controllability of CC, for instance by using alternative techniques for measuring attentional orientation, such as event-related potentials24, fMRI or/and eye-tracking25.…”
Section: Discussionmentioning
confidence: 99%
“…These results, jointly with the current data, are compatible with the hypothesis that contextual cuing of visual search is not supported by uncontrollable attentional orientation towards the target in repeated trials. This idea will benefit from future research examining the controllability of CC, for instance by using alternative techniques for measuring attentional orientation, such as event-related potentials24, fMRI or/and eye-tracking25.…”
Section: Discussionmentioning
confidence: 99%
“…More surprisingly, CC is non-existent in amnesic patients with major damage to MTL structures [34,35]. Given that IL is thought to be independent of the MTL, this result received great interest in the literature [16,[36][37][38][39] (Box 2). Despite apparent contradictions, this literature leads to the conclusion that the MTL plays a crucial role in implicit CC and that, although not required, the hippocampus might also be engaged even when knowledge remains implicit [16].…”
Section: Reviewmentioning
confidence: 90%
“…There is a general consensus that repeating the context triggers rapid reductions in entorhinal/perirhinal cortical activation, regardless of performance in subsequent recognition memory (e.g., [36,37,39], or [38] for a different result with scenes). This rapid reduction in anterior MTL cortex has been ascribed to memory for repeated visuospatial configurations, and more generally to the integration of elements of experience into fused representations, in other words into chunk formation [37].…”
Section: Box 2 Neural Bases Of CCmentioning
confidence: 98%
“…Three specific findings observed in experiments using synthetic displays are pertinent for the present study. First, studies of contextual cueing have provided neuropsychological and fMRI evidence that this form of learning relies on the hippocampus (Chun & Phelps, 1999; Greene, Gross, Elsinger, & Rao, 2007; Manelis & Reder, in press), a structure typically associated with declarative long-term memory (e.g., Moscovitch, Nadel, Winocur, Gilboa, & Rosenbaum, 2006; Squire, 1992). Second, electrophysiological studies have shown that visual cortical responses that are typically modulated by spatial attention are also enhanced for previously viewed configurations compared novel configurations (Johnson, Woodman, Braun, & Luck, 2007; Olson, Chun, & Allison, 2001).…”
Section: Introductionmentioning
confidence: 99%